Respuesta :

MathQ

Answer:

x=-5

Step-by-step explanation:

2(5x-4)=10x-8

-3(3x-1)=-9x+3

10x-8-9x+3

x=-5

The answer you are looking for is -5.

Writing out the equation,

2(5x-4)-x-3(3x-1)

Using the Distributive Property for 2(5x-4) and -3(3x-1),

10x-8-x-9x+3

Using the Associative Property,

10x-x-9x-8+3

Simplifying the similar terms,

9x-9x-8+3

Canceling both "9x" terms, since 9x-9x is obviously 0,

0-8+3, or simply just -8+3.

-8+3=-5

So, therefore the final answer is -5.

I hope that this has helped you. Enjoy your day, and take care.